Use of edible coatings based on hydroxypropyl methylcellulose and beeswax in the conservation of red guava 'Pedro Sato'. (30th August 2019) - Formiga, Anderson S.; Pinsetta, José S.; Pereira, Emmanuel M.; Cordeiro, Isabela N.F.; Mattiuz, Ben-Hur
Highlights: Edible coatings based on HPMC + BW delay fruit maturation and softening. HPMC + 20% BW coating extended in 6 d the shelf life of 'Pedro Sato' guavas. Coated guavas chlorophylls content decreases according to increased BW concentration. The balance between HPMC and BW improves the properties of the coatings. Abstract: Guavas are tropical climacteric fruit with a short postharvest shelf life at room temperature. This study aims to extend the shelf life of red guavas 'Pedro Sato' using edible coatings of hydroxypropyl methylcellulose (HPMC) and beeswax (BW) at concentrations of 10%, 20%, and 40% (dry basis). Coated and uncoated guavas were stored for 8 days at 21 °C and assessed every 2 days. The HPMC + BW produced a modified atmosphere around the fruit, delaying ripening process. The coatings reduced loss of mass, maintained green color, and increased firmness compared to the control fruit. The uncoated fruit had 6 days of shelf life. The treatment with HPMC + 20% BW provided the best maintenance of fruit quality. On the eighth day, fruit with this coating showed the same physicochemical characteristics of control fruit in the second day of storage, which represents a gain of 6 days in the shelf life of guavas 'Pedro Sato'.